LEGAL GUARANTEES OF HUMAN AND CIVIL RIGHTS IN UKRAINE - Бородін, Іван Лук`янович; Близнюков, Іван Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: is to clarify the concept, essence, legal guarantees of human and civil rights and freedoms, taking into account modern legal approaches. Methods: comparison, analysis, induction, deduction, and others that served as a tool for material selection and were a necessary condition for achieving this goal. Results: the article considers legal guarantees of human and civil rights and freedoms in Ukraine. The practical and theoretical functioning of the main responsibilities of the state to guarantee human and civil rights is substantiated, as well as the world experience of protection of human and civil rights and freedoms in the international arena is summarized. Discussion: human and civil rights and freedoms are one of the most important social values, the main object of most constitutional and legal relations. The effectiveness of their implementation, use and compliance depend on the level of their protection and security. In view of this, a valuable part of the constitutional - legal status of man and citizen are the guarantees of these rights and freedoms. The article considers the main legal guarantees of human and civil rights in Ukraine and their legal basis. In addition, the system of international legal guarantees and the main ways to protect their rights in the European Court of Human Rights are analyzed. Important principles of a democratic state governed by the rule of law are recognized as constitutionally enshrined human rights and freedoms, as well as the means provided by law for their protection. The main feature of legal guarantees is that they are reflected in the current legislation in the form of special tools and methods to ensure the rights and responsibilities of all citizens of the country. The purpose of guarantees is that they are designed to provide a more favorable environment in the atmosphere in which the constitutions and laws enshrine the legal status of the individual and, especially, his rights and freedoms, in their implementation, would become the de facto position of each individual and citizen. In the international legal arena, it is the guarantees of human and civil rights and freedoms that play the role of real opportunities for implementation and protection in this area. In view of this, the urgent task is to establish the essence of guarantees of human and civil rights and freedoms, determine the list of rights to be guaranteed by constitutional means, and approve the limits of these guarantees provided in the Basic Law of Ukraine.